2015
DOI: 10.1002/anie.201501193
|View full text |Cite
|
Sign up to set email alerts
|

Red, Green, and Blue Luminescence by Carbon Dots: Full‐Color Emission Tuning and Multicolor Cellular Imaging

Abstract: A facile approach for preparation of photoluminescent (PL) carbon dots (CDs) is reported. The three resulting CDs emit bright and stable red, green and blue (RGB) colors of luminescence, under a single ultraviolet-light excitation. Alterations of PL emission of these CDs are tentatively proposed to result from the difference in their particle size and nitrogen content. Interestingly, up-conversion (UC)PL of these CDs is also observed. Moreover, flexible full-color emissive PVA films can be achieved through mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
1,136
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,638 publications
(1,199 citation statements)
references
References 51 publications
38
1,136
3
2
Order By: Relevance
“…The data of J sc , V oc , and FF for these devices are shown in Figure 7 and compiled in Table 4. The results indicate that the individually N719-sensitized device achieves a η value of 5.14% (with J sc = 13.26 mA/cm 2 , V oc = 0.66 V, and FF = 0.58), while the devices individually sensitized by L 1 , L 2 , and L 3 were found to show a low η value of 0.26% (with J sc = 1.77 mA/cm 2 (Table 4), it was found that the η values of these devices L 1 /N719, L 2 /N719, L 3 /N719, Zn3/ N719, and Hg3/N719 are 6.73%, 6.96%, 7.25%, 6.62%, and 5.70%, respectively, that is, cells individually sensitized by N719 (5.14%) show relatively lower efficiency. On the basis of the results of the above data, there is a dramatic influence of the substituent group and coordination on the DSSCs performance, and the η values increase in the order L 1 /N719 < L 2 / N719 < L 3 /N719 and Hg3/N719 < Zn3/N719 < L 3 /N719.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The data of J sc , V oc , and FF for these devices are shown in Figure 7 and compiled in Table 4. The results indicate that the individually N719-sensitized device achieves a η value of 5.14% (with J sc = 13.26 mA/cm 2 , V oc = 0.66 V, and FF = 0.58), while the devices individually sensitized by L 1 , L 2 , and L 3 were found to show a low η value of 0.26% (with J sc = 1.77 mA/cm 2 (Table 4), it was found that the η values of these devices L 1 /N719, L 2 /N719, L 3 /N719, Zn3/ N719, and Hg3/N719 are 6.73%, 6.96%, 7.25%, 6.62%, and 5.70%, respectively, that is, cells individually sensitized by N719 (5.14%) show relatively lower efficiency. On the basis of the results of the above data, there is a dramatic influence of the substituent group and coordination on the DSSCs performance, and the η values increase in the order L 1 /N719 < L 2 / N719 < L 3 /N719 and Hg3/N719 < Zn3/N719 < L 3 /N719.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fluorescent carbon dots (CDs), as a new type of carbon nanomaterials with sizes of less than 10 nm, have attracted tremendous attention in diverse research fields recently [1][2][3]. Compared with some conventional semiconductor quantum dots with heavy metal cores, CDs are superior in terms of low cytotoxicity, excellent aqueous solubility, good biocompatibility, broader photoluminescence profiles, and high photostability [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…CQDs emit blue light, with an exception of a few studies reporting longer wavelength emissions (such as the emission of red light) [31,[43][44][45]. Interestingly, the main product of the CQDs (sample IV) could emit yellow light, as evidenced from Fig.…”
Section: Spectroscopic Properties Most Of the Previous Studies On Cqdmentioning
confidence: 88%